Cancer Proteomics From Bench to Bedside - Daoud, Sayed S.; Daoud, Sayed S. (Cancer Drug Discovery and Development, 2008)
Over the past 20 years or so, there have been tremendous advances in our understanding of how normal cells transform to cancer and the importance of signaling pathways in cancer initiation and progression. Therefore, proteomics technologies must be improved for more global analysis of protein content of cells, tissues and body fluids as well as the posttranslational modifications to allow for proper detections and validation. In Cancer Proteomics, the authors collectively provide the current status of proteomics in cancer therapy and offers the existing technologies used in proteomics that allow for protein profiling and for the identification of druggable targets in human samples. Mass spectrometry based protein characterization and protein microarrays hold great promise of predicting response to specific drugs in cancer therapy. Insightful to the reader with broad perspectives on topics related to the use of proteomic strategies in cancer therapy, Cancer Proteomics offers anticipated challenges that may arise from its application in daily practice.